Strength of carbon fiber/epoxy in sea water - Yuncuoglu, Ercument Ugur; Ince, Serdar Turgut; Bagci, Eyup (WALTER DE GRUYTER GMBH, 2021)
Composite materials are widely used in the marine industry. The marine environment, on the other hand, has a significant impact on the strength of composite materials. The tensile strength is adversely affected because the matrix material absorbs water. In this study, the effect of orientation, number of layers and different mediums over time on the tensile strength of the woven carbon fiber reinforced epoxy composite material was investigated experimentally from a comprehensive perspective. The findings of the experiments were subjected to variance analysis. The repeated tests and cross-results of the experimental parameters were found to be compatible with each other. Seawater reduces the tensile strength of composite materials in any case. The tensile strength increased with increasing the number of layers. However, it has been observed that the seawater medium reduces strength when the number of layers increases. At the same time, as orientation angle rises, the seawater medium's negative effect on strength rises.
Keywords: Composite material; strength; water absorption; carbon fiber reinforced composite; MECHANICAL-PROPERTIES; GLASS; ENVIRONMENT; SEAWATER; COMPOSITES; PERFORMANCE; Materials Science